Development of the SMIQ questionnaire measuring interest, sense of self-efficacy and perception of the links existing between mathematics and science in an integrated context - Béchard, Nathan; Langlois, Simon; Poliquin, Guillaume; Cyr, Stéphane (Mesure et évaluation en éducation, 2021)
The integration of academic disciplines such as science and mathematics (M&S) can help foster students’ interest and sense of self-efficacy (S-E). However, few questionnaires appear to have been developed to measure these perceptual variables in this type of context. Nor do any appear to exist that are suitable for elementary students from low-income and multicultural schools. This article reports the results of the validation process of such a questionnaire comprising six scales conducted among 1,553 Grade 5 or 6 students from schools in Canada’s Montréal area. In its final version, the Science and Mathematics Integration Questionnaire (SMIQ) measures six perceptual variables: S-E in science, S-E in mathematics, interest in science, interest in mathematics, interest in integrated M&S activities and perception of the links between science and mathematics. To our knowledge, the last two variables have never been measured and the proposed scales to measure them are new.